2020
DOI: 10.1016/j.eplepsyres.2020.106345
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of visual evoked potentials related to the electro-clinical expression of reflex seizures in photosensitive patients with idiopathic occipital lobe epilepsy

Abstract: Characteristics of visual evoked potentials related to the electro-clinical expression of reflex seizures in photosensitive patients with idiopathic occipital lobe epilepsy,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Several observations indicate that the occipital cortex or visual system in patients with photosensitive epilepsy is hyperexcitable. Visual evoked potentials (VEPs) have a higher amplitude in photosensitive patients with generalized or occipital lobe epilepsies when compared to healthy controls or patients without photosensitive epilepsy 198,201–203 . The increase in VEP amplitude depends on factors such as the contrast of the stimuli used and eye closure.…”
Section: Mechanisms Of Photosensitivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Several observations indicate that the occipital cortex or visual system in patients with photosensitive epilepsy is hyperexcitable. Visual evoked potentials (VEPs) have a higher amplitude in photosensitive patients with generalized or occipital lobe epilepsies when compared to healthy controls or patients without photosensitive epilepsy 198,201–203 . The increase in VEP amplitude depends on factors such as the contrast of the stimuli used and eye closure.…”
Section: Mechanisms Of Photosensitivitymentioning
confidence: 99%
“…Visual evoked potentials (VEPs) have a higher amplitude in photosensitive patients with generalized or occipital lobe epilepsies when compared to healthy controls or patients without photosensitive epilepsy. 198,[201][202][203] The increase in VEP amplitude depends on factors such as the contrast of the stimuli used and eye closure. In addition, VEPs in patients with photosensitive epilepsy respond differently to repetitive transcranial magnetic stimulation (rTMS) than VEPs in controls.…”
Section: Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Low-frequency visual evoked potentials (VEP) is mostly limited for testing the functional integrity of the visual system (47), and is less explored in epilepsy. Studies in patients with photosensitive occipital lobe epilepsy reported increased VEP amplitudes consistent with hypersynchrony (48, 49), and abnormal latencies possibly due to failure of cortical gain control (48). VEP may be a valuable tool to investigate brain excitability, especially sub-seizure-threshold network dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Each frequency was tested by separate trains of flashes with an inter-stimulus free period of five seconds, with eyes opened, eyes closed, and during eye closure. Pattern sensitivity was tested using a standard procedure of stimulation, according to recommended guidelines [17] , as reported elsewhere [18]. Briefly, we used three types of black-and-white full-field pattern (checks, horizontal stripes, vertical stripes), two black-andwhite hemi-field patterns (left and right, horizontal stripes), and one red/blue full-field pattern (horizontal stripes).…”
Section: Commission On Classification and Terminology Commission Of T...mentioning
confidence: 99%